O desenvolvimento de projetos interdisciplinares na educação básica como estratégia para o fortalecimento de aprendizagens significativas, dialogicidade e protagonismo estudantil - Mendonça, Raylany Wedna Alves (2021)
The understanding of science, technology and innovation is fundamental for the education of children, young people and adults, as the construction of this knowledge will directly influence their lives, insertion, posture, contributions and vision of the world for and in modern society. Project work is an alternative for the consolidation of significant learning, fostering protagonism and developing criticality and reflexivity. The work on screen aims to explain the results of a project developed by teachers and students of Basic Education in a school in the State Education Network of Pernambuco. Regarding the project's contributions to students at this time of remote learning, 76.5% of students answered yes and justified that the project helped to strengthen contact, companionship, facilitated learning, carrying out activities and even organization of study routines and schedules. The project's actions enabled the existence of new institutional bonds. Partnerships established, for example, with the Federal University of Pernambuco and the Federal Institute of Pernambuco, which strengthened practices, brought basic education closer to higher education and indicated paths and alternatives that promoted gains for Education.